EVALUATION OF CONTEXTUAL CLUES: EFL PROFICIENCY IN READING COMPREHENSION - Stevani, Margaret; Prayuda, Meikardo Samuel; Sari, Dyan Wulan; Marianus, Sumarlin Mangandar; Tarigan, Karisma Erikson (University of Kuningan, 2022)
The present research evaluated EFL perspectives about contextual clues in reading comprehension at different proficiency levels. The data analysis using qualitative descriptions with frequencies and percentages was employed for 38 intermediate-level students and 25 advanced-level students in the university level through teaching contextual clues in reading comprehension with an experimental design. The results proved that students' proficiency in reading ability could be demonstrated by their use of idiomatic expressions, indirect language, direct language, series of words, comparison, synonym, tone, situation, mood, reference, restatement, preposition, cause-effect, modification, and example. Advanced students with a high level of vocabulary, grammar, and decoding skills were better able to utilize many contextual clues than intermediate students. Thus, reading ability was strongly correlated with the ability to infer word meaning from contextual clues.